Removal of Cr(Vi) by Ultrafiltration Enhanced by a Cellulose-Based Soluble Polymer - Sanchez-Poblete, J; Roa-Ruiz, K; Oyarce-Riveros, E; Boulett-Neira, A; Boulett-Neira, A (Elsevier Ltd, 2023)
In this study, polymer-enhanced ultrafiltration (PEUF) was used to remove chromium ions (Cr(VI)) from water using quaternized hydroxyethyl cellulose ethoxylate (QHECE) as the extracting agent. The polymer was structurally and thermally characterized before and after loading, where Fourier transform spectra were used to corroborate the Cr(VI) binding sites. Thermogravimetric analysis showed an increase in the residual mass due to the formation of macromolecular aggregates from the water-soluble polymer (WSP) and Cr(VI). SEM/EDX was used to corroborate the presence of Cr(VI) on the WSP surface. The washing method was used to study Cr(VI) retention as a function of the solution pH, WSP quantity, pressure, Cr(VI) concentration, membrane type and presence of interfering ions (NaCl, Na2SO4 and NaHPO4) at three Cr(VI):interferent molar ratios (1:1, 1:2 and 1:4). In addition, the polymer reusability was studied over six sorption-desorption cycles. Next, the enrichment method was used to determine the maximum retention capacity of the polymer. Finally, PEUF was used to test Cr(VI) removal in simulated industrial electroplating wastewater. By varying different parameters, 92 % retention efficiency was achieved at pH 9.0 using a polymer mass of 50 mg, a pressure of 2.0 bar, an initial Cr(VI) concentration of 30 mg L−1 and a 10-kDa regenerated cellulose membrane. Increasing the Cr(VI):interferent molar ratio was found to decrease the retention efficiency, and significant decrease was obtained for the highest ratio of sulfonate ions to Cr(VI) used. Finally, the maximum retention capacity was determined to be 299.46 mg g−1 using the enrichment method, and it was demonstrated that the polymer could be reused for up to four consecutive sorption-desorption cycles. © 2023 Elsevier Ltd